The Effect of Problem Oriented Project Based Learning Model Assisted by Artificial Intelligence in Biology Learning on Science Literacy and Collaboration Skills of Grade XI MA Students - Adawiyah, Rabiatul; Ibrohim, Ibrohim; Prabanintyas, Sitoresmi (BIOEDUSCIENCE, 2025)
Background: Science literacy and collaboration skills are skills that students must be empowered with in the 21st century. Science literacy refers to understanding science issues and applying them in everyday life, while collaboration skills relate to the ability to work together to achieve goals or solve problems. Students must have these abilities so that empowering them can be done by applying innovative learning methods, strategies or models. POPBL is one of the models that can develop the skills needed by students. The effectiveness of the POPBL model is expected to increase with the integration of Aritifical Intelligence (AI). The role of AI as a tool to facilitate students in learning. This study aims to determine the effect of the AI-assisted POPBL model on science literacy and collaboration skills on circulatory system and respiratory system material. Methods: The research method used was quasi-experiment with nonrandomised control group pretest-posttest design. Involving three treatment classes namely POPBL class assisted by AI, POPBL, and regular class (lecture and assignment method). The instruments used were science literacy questions and collaboration skills questionnaire. Data analysis used ANCOVA test, before that the prerequisite test was carried out, namely homogeneity test and normality test. Results: The prerequisite tests conducted proved that the data were normally distributed and the data variance was homogeneous. The results of the ANCOVA data analysis value have a significance value of the learning model treatment which is p-value = 0.000. This shows that AI-assisted POPBL has an effect on science literacy and collaboration skills Conclusion: AI-assisted POPBL has an effect on science literacy and collaboration skills.